Clostridium difficile ribotype 176 – A predictor for high mortality and risk of nosocomial spread?. (August 2016) - Polivkova, Sylvia; Krutova, Marcela; Petrlova, Katarina; Benes, Jiri; Nyc, Otakar
Abstract: Purpose: The objective of this survey was to determine the incidence of Clostridium difficile infections (CDI) at the Department of Infectious Diseases, Bulovka Hospital, and to evaluate clinical and epidemiological data on CDI patients together with a detailed molecular characterisation of C . difficile isolates. The patient outcomes were correlated to causative C . difficile PCR-ribotype. Methods: The twelve-month study (2013) comprised patients two years of age and older with CDI. CDI severity was estimated using ESCMID criteria and ATLAS scoring. C . difficile isolates were further characterized using ribotyping, Multiple-Locus Variable Tandem-Repeats analysis (MLVA) and investigation of antibiotic-resistance determinants ( gyrA, gyrB, rpoB, ermB ). Results: A total of 619 diarrhoeal stools were investigated. Seventy-two stool samples were GDH and toxin A/B positive, and 39 samples were GDH positive only and subsequently toxigenic C . difficile was cultured. In total, 111 C . difficile isolates were characterized, of which 64 (57.7%) belonged to PCR-ribotype 176. MLVA analysis of PCR-ribotype 176 isolates revealed 11 clonal complexes. Seventy-two isolates (64.9%) showed amino acid substitution Thr82Ile in the GyrA, and sixty-two isolates (55.9%) showed amino acid substitutions Arg505Lys together with His502Asn, or Asp492Glu together with Arg505Lys in the RpoB . Twelve isolates (10.8%) were ermB positive. Severe CDI according to the ESCMID criteria was recorded in forty-two patients (37.8%), and sixteen patients (14.4%) had ATLAS score ≥ 6. Twenty-nine patients (26.1%) had recurrent CDI and twenty-four patients (21.6%) died during the study period. Conclusions: A higher rate of severe CDI, recurrences and mortality in association with PCR-ribotype 176 infections were observed. The high incidence of PCR-ribotype 176 in the study, and the presence of clonal relatedness between PCR-ribotype 176 isolates, indicate its higher capacity to spread in a hospital setting, which in turn highlights the need to implement strict epidemic measures when PCR-ribotype 176 occurs. Highlights: A twelve-month study was performed at a specialised infectious disease centre. A high occurrence of RT176 (57.7%) was found. High recurrence rate (26.1%) and mortality rate (21.6%) were observed. Higher rate of severe CDI, recurrence and mortality was associated with RT176.